Radial Artery Occlusion After Transradial Interventions: A Systematic Review and Meta‐Analysis. Issue 1 (25th January 2016) - Rashid, Muhammad; Kwok, Chun Shing; Pancholy, Samir; Chugh, Sanjay; Kedev, Sasko A.; Bernat, Ivo; Ratib, Karim; Large, Adrian; Fraser, Doug; Nolan, James; Mamas, Mamas A.
Abstract : Background: Radial artery occlusion (RAO) may occur posttransradial intervention and limits the radial artery as a future access site, thus precluding its use as an arterial conduit. In this study, we investigate the incidence and factors influencing the RAO in the current literature. Methods and Results: We searched MEDLINE and EMBASE for studies of RAO in transradial access. Relevant studies were identified and data were extracted. Data were synthesized by meta‐analysis, quantitative pooling, graphical representation, or by narrative synthesis. A total of 66 studies with 31 345 participants were included in the analysis. Incident RAO ranged between <1% and 33% and varied with timing of assessment of radial artery patency (incidence of RAO within 24 hours was 7.7%, which decreased to 5.5% at >1 week follow‐up). The most efficacious measure in reducing RAO was higher dose of heparin, because lower doses of heparin were associated with increased RAO (risk ratio 0.36, 95% CI 0.17–0.76), whereas shorter compression times also reduced RAO (risk ratio 0.28, 95% CI 0.05–1.50). Several factors were found to be associated with RAO including age, sex, sheath size, and diameter of radial artery, but these factors were not consistent across all studies. Conclusions: RAO is a common complication of transradial access. Maintenance of radial patency should be an integral part of all procedures undertaken through the radial approach. High‐dose heparin along with shorter compression times and patent hemostasis is recommended in reducing RAO.